Efficient marker‐assisted backcross conversion of seed‐parent lines to cytoplasmic male sterility. Issue 1 (6th December 2012) - Herzog, Eva; Frisch, Matthias; Piepho, H.‐P.
Abstract For many crops, cytoplasmic male sterility (CMS) is a cornerstone of hybrid production. Efficient conversion of elite lines to CMS by marker‐assisted backcrossing is therefore desirable. In contrast to gene introgression, for which donor segments around target genes have to be considered, background selection for CMS conversion focuses solely on recovery of the recurrent parent genome. The optimal selection strategies for CMS conversion will consequently differ from those for gene introgression and have not yet been investigated. The objectives of our study were to evaluate and optimize the resource requirements of CMS conversion programmes and to determine the most cost‐effective use of single‐marker (SM) and high‐throughput (HT) assays for this purpose. We conducted computer simulations for CMS conversion of genetic models of sugar beet, rye, sunflower and rapeseed. CMS conversion required fewer resources than gene introgression with respect to population size, marker data points and number of backcross generations. Combining HT assays in early backcross generations with SM assays in advanced backcross generations further increased the cost‐efficiency of CMS conversion for a broad range of cost ratios.